The Role Of The Community @toleranci.id In Religious Moderation In Social Media Instagram - Siagian, Tri Uci Rahmayani; Saburi, Annai (UNIVERSITAS PAKUAN, 2023)
This research aims to understand the role of the @toleransi.id community in religious moderation on Instagram social media. Research is a qualitative descriptive study. This study is a type of content analysis. Data sources in this study include primary data and secondary data. The technique of data collection in this research is by performing observations and documentation. These research data analysis techniques include data reduction, data presentation, and data verification. The results of this study show that religious moderation is respecting the values of goodness and upholding humanity, so the tendency to practice religious teachings is sometimes exaggerated, often leaving the truth one-sided. And studying religious moderation is very important because often people assume that believing themselves is the most right and others are wrong. Therefore, we must know that the purpose of religious moderation is to create a society that is always peaceful without having to argue with one another. Religious moderation also does not mean that everyone should follow the teachings of other religions, but religious Moderation teaches how to respect and respect the religion of others in a good and respectful way. A religious community of moderation that brings positive thoughts and activities will be welcomed by every community if their side also respects the person and it is one of the absolute attitudes in mankind.